2015
DOI: 10.1128/iai.00275-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CPAF Critical Residues and Secretion during Chlamydia trachomatis Infection

Abstract: CPAF (chlamydial protease-like activity factor), a Chlamydia serine protease, is activated via proximity-induced intermolecular dimerization that triggers processing and removal of an inhibitory peptide occupying the CPAF substrate-binding groove. An active CPAF is a homodimer of two identical intramolecular heterodimers, each consisting of 29-kDa N-terminal and 35-kDa C-terminal fragments. However, critical residues for CPAF intermolecular dimerization, catalytic activity, and processing were defined in cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…survival in the mouse lower genital tract whereas a similar transformation performed with a mCherry-expressing control plasmid failed to do so. The significant but partial rescue of the chlamydial infectivity by the CPAF complementation may have been a consequence of either the interference from the excessive amount of the incompletely processed CPAF fragments in the complemented strain (38,(40)(41)(42)44) or a CPAF-independent defect inherited in the parental L2-17 strain (34). Nevertheless, the complementation experiments have demonstrated that the failure of L2-17 to survive in the mouse lower genital tract was at least partially due to the lack of CPAF.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…survival in the mouse lower genital tract whereas a similar transformation performed with a mCherry-expressing control plasmid failed to do so. The significant but partial rescue of the chlamydial infectivity by the CPAF complementation may have been a consequence of either the interference from the excessive amount of the incompletely processed CPAF fragments in the complemented strain (38,(40)(41)(42)44) or a CPAF-independent defect inherited in the parental L2-17 strain (34). Nevertheless, the complementation experiments have demonstrated that the failure of L2-17 to survive in the mouse lower genital tract was at least partially due to the lack of CPAF.…”
Section: Discussionmentioning
confidence: 92%
“…CPAF is a unique serine protease (38)(39)(40)(41)(42) that is secreted into the host cell cytosol via a sec-dependent type II secretion pathway (34,43). We have recently validated the secretion of CPAF into the host cell cytosol (44). To further investigate the role of CPAF in chlamydial pathogenesis, we took advantage of chemically derived C. trachomatis L2 mutants (34,45,46) and compared a CPAF-deficient C. trachomatis strain to a control strain derived by lateral gene transfer (34) for survival in the mouse genital tract.…”
mentioning
confidence: 99%
“…The intrainclusion C. trachomatis organisms are known to secrete various proteins, including CPAF and Pgp3, into host cell cytosol (2,20,33,(44)(45)(46). Both CPAF and Pgp3 are accumulated in large quantities in the cytosol of the infected cells prior to the lysis of the infected cells (18,20). Thus, we hypothesize that the prestored CPAF and Pgp3 in the host cell cytosol can be rapidly released to target extracellular antimicrobial peptides upon cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…The strong antibacterial activity of AMPs has selected many bacterial species to evolve countermeasures for evading the same defense mechanism (15)(16)(17). We have recently shown that the chlamydial chromosome-encoded serine protease CPAF, which is secreted out of the chlamydial inclusion (18), can degrade LL-37 and neutralize its antichlamydial activity (19).…”
mentioning
confidence: 99%
“…It is known that C. trachomatis organisms can secrete numerous proteins into host cell cytoplasm [18,19]. Among them, Chlamydial Protease-Like Activity Factor (CPAF), a chlamydial type II secretion protein, may serve as a promising candidate of virulence factor as proposed [16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%